Implementation of e-Learning Module Based on Science Technology Engineering Mathematics on Solar Cells Topic - Mairi Sukma; Abdul Halim; Evendi Evendi (STKIP Singkawang, 2022)
This study was conducted to test the validity, practicality and effectiveness of implementing STEM-based e-learning modules on the topic of solar cellss to be used as teaching materials for students. This research was conducted at the Unsyiah Physics Education Study Program. The research method used is the Quasi Experiment method, pretest-posttest control group design. The module validity data were analyzed using a validation sheet. The results showed that the STEM-based e-learning module was valid. The practicality of the module was analyzed using activity observation sheets and student response sheets. The results showed that the implementation of STEM-based e-learning modules was practical to increase student activity and received positive responses from students. The effectiveness of the module was analyzed using the Three Tier diagnostic test using the CRI index, comparing the pretest results with the posttest result, and tested for significance through the two-mean difference test using the independent sample t-test. The results showed that implementsi e-learning modules on topic STEM-based solar cellss are effective to reduce the level of misconceptions and may improve learning outcomes (N-gain) student.